(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This research was done to find out how adding hydrated lime and extra water content to clayey soil samples affecting their unconfined compressive strength (UCS). The clayey soil is a locally available soil from the clayey soil area in Cyrene, northeastern of Libya. In the soil samples, hydrated lime (HL) was added at a rate of 5% of the dry weight of the soil. The standard compaction test was conducted on the untreated natural soil sample “NS” so that the optimum water content at the maximum dry density can be determined wop1. Because of the addition of hydrated lime to the soil will affect the dry density-water content relationship, the standard compaction test was conducted again on the treated soil sample “NS+5%HL” to determine another optimum water content wop2. These optimum water values wop1 =17.8 & wop2=19.5 will be used to prepare unconfined compressive strength specimens. In the experimental work two soil mixtures will be used beside the natural soil mixture. The first mixture "NS+5%HL+wop1" and the second mixture "NS+5%HL+wop2" were prepared in addition to the natural soil mixture "NS+wop1". All unconfined compressive strength specimens for the first and second mixtures were extracted and tested at 7 and 14 days of curing, then comparison were made. The first mixture, "NS+5%HL+wop1" will be compared with the natural soil mixture, "NS+ wop1" in order to understand the impact of HL addition. The effect of the water content changing can be seen when the second mixture, "NS+5%HL+wop2" is compared with the first mixture, NS+5%HL+wop1. According to the findings, Although the first mixture’s specimens have the least dry density value, the UCS values increased by 218.5 and 386.5% at 7 and 14 days of curing, respectively, when compared to the natural soil mixture. This illustrates the result of the added hydrated lime. At curing times of 7 and 14 days, respectively, the UCS values for the second mixture fell by 8.61 and 14.11% when compared to the first mixture. And this illustrates the impact of variations in water content.